THE PROTECTION OF THE EUROPEAN TRADEMARK IN THE LIGHT OF THE EU REGULATION 2015/2424 OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL - C.I. Murzea; Roxana Matefi (My University, 2017)
The present paper aims to analyze the novelty aspects brought about by the EU Regulation 2015/2424 of the European Parliament and of the Council which came into force March 23rd, 2016, regarding the trademark, especially aspects regarding its protection and the rights it provides, as opposed to national law and the old community law. We will consider both theoretical aspects, as well as jurisprudence issues in this domain.